DECREASED ANXIETY IN MOTHER OF CHILDREN WITH STUNTING AFTER THOUGHT STOPPING THERAPY: DOI: https://doi.org/10.35654/ijnhs.v2i2.94 - Ika Juita Giyaningtyas; Achir Yani Syuhaimie Hamid (Alta Dharma Publisher, 2019)
Anxiety is an uncertain and unwell-defined worry experienced by individuals. Physicall illnesses is one of anxiety causes. Stunting is a physicall illness in children manifested by a very low height for age. Stunting causes cognitive development disorder, inhibition of mental and motor development, make children more susceptible to diseases. Stunting bad effects is not only on children with stunting but also for parents of children with stunting who become caregiver for the children. Stigma from the society can be occur to the family who cares children with stunting, especially mother. Preliminary data showed mothers of children with stunting feels worry or anxiety about their children. Anxiety intervention for mothers of children with stunting is necessary. Anxiety intervention conducted by thought stopping. Based on the data, this study conducted to know decrease in anxiety in mother of children with stunting after tought stopping therapy. The method was a case study. Author conducted thought stopping therapy in three times of meeting. The result of the study was thought stopping can be used as psychotherapy to decrease anxiety in mother of children with stunting. Nurse have to consider client ability in change the tought proccess by concern on emotional level and sentitifity.